Concise paediatrics - Sidwell, Rachel U.; Thomson, Mike (Mike Andrew) (Boca Raton, FL : CRC Press, 2017)
Concise Paediatrics,Second Editionis essential reading for all postgraduates training in paediatrics, particularly when preparing for the MRCPCH exam, and for general practice trainees preparing for the DCH exam. As a comprehensive but concise reference to any condition they are likely to encounter on the wards or in the accident and em
OCLC-licensed vendor bibliographic record.
Keywords: Pediatrics; MEDICAL / General; MEDICAL / Pediatrics